New alternatives for laser vaporization of the prostate: experimental evaluation of a 980-, 1,318- and 1,470-nm diode laser device - Wezel, Felix; Wendt-Nordahl, Gunnar; Younsi, Nina; Bach, Thorsten; Weiß, Christel; Michel, Maurice Stephan; Häcker, Axel (World journal of urology, 2010)
Several diode laser systems were introduced in recent years for the minimal-invasive surgical therapy of benign prostate enlargement. We investigated the ablation capacities, hemostatic properties and extend of tissue necrosis of different diode lasers at wavelengths of 980, 1,318 and 1,470 nm and compared the results to the 120 W GreenLight™ HPS laser.